Full-length transcriptome sequencing analysis and characterization, development and validation of microsatellite markers in Kengyilia melanthera - Xiong, Yanli; Yang, Jian; Xiong, Yi; Zhao, Junming; Liu, Lin; Liu, Wei; Sha, Lina; Zhou, Jiqiong; You, Minghong; Li, Daxu; Lei, Xiong; Bai, Shiqie; et al. (Frontiers in Plant Science, 2022)
As a typical psammophyte of the Triticeae, Kengyilia melanthera possesses high feeding potential and great utilization values in desertification control in the Qinghai-Tibet Plateau. However, few gene function and genetic studies have been performed in K. melanthera. In this study, single-molecule real-time sequencing technology was used to obtain the full-length transcriptome sequence of K. melanthera, following the functional annotation of transcripts and prediction of coding sequences (CDSs), transcription factors (TFs), and long non-coding RNA (lncRNA) sequences. Meanwhile, a total of 42,433 SSR loci were detected, with 5'-UTRs having the most SSR loci and tri-nucleotide being the most abundant type. In total, 108,399 SSR markers were designed, and 300 SSR markers were randomly selected for diversity verification of K. melanthera. Forty-nine polymorphic SSR markers were used to construct the genetic relationships of 56 K. melanthera accessions, among which 21 SSR markers showed good cross-species transferability among the related species. In conclusion, the full-length transcriptome sequence of the K. melanthera will assist gene prediction and promote molecular biology and genomics research, and the polymorphic SSR markers will promote molecular-assisted breeding and related research of K. melanthera and its relatives.